Bureaucracy : a key idea for business and society - Vine, Tom (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Bureaucracy is a curse-- it seems we can't live with it, we can't live without it. It is without doubt one of the fundamental ideas which underpin the business world and society at large. In this book, Tom Vine observes, analyses and critiques the concept, placing it at the heart of our understanding of organisation. The author unveils bureaucracy as an endlessly emergent phenomenon which defies binary debate-- in analysing organisation, we are all bureaucrats. In building an experiential perspective, the book develops more effective ways to interact with bureaucracy in theory and practice. Empirical material take centre stage, whilst the book employs ethnographic and auto-ethnographic methods to illuminate the existential function of bureaucracy. Taking examples from art, history and culture, this book provides an entertaining alternative academic analysis of bureaucracy as a key idea in business and society which will be essential reading for students and scholars of work and organisation
OCLC-licensed vendor bibliographic record.
Keywords: Bureaucracy; Interorganizational relations; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Organizational Behavior